KAJIAN GERAKAN PENSEJAHTERAAN EKONOMI MASYARAKAT PESISIR (G-PEMP) DI SUMATERA BARAT - Kamal, Eni (Publikasi Penelitian Terapan dan Kebijakan, 2013)
The area scope of study implementation ocean and fisheries (G-PEMP) un west Sumatera. Include 7 district/city coast; Pasaman Barat, Agam, Padang Pariaman, Pariaman, Padang, Pesisir Selatan, and the Mentawai Islands, which include 42 coastal districts and 89 coastal villages. From 42 districts and 89 villages deliberately determined several districts and villages in each district / citybased on criteria that could support the success of the program G-PEMP. Policy recommendations on activities of G-PEMP in West Sumatra covered 4 activities; capture fisheries package program, aquaculture package, handling/processing product package, and marketing of fishery products package.